Arsenic and Fluoride in surface water (Chasico Lake, Argentina) - Fernandez Cirelli, Alicia (2014)
Chasicó Lake is the main water body in the southwest of the Chaco-Pampean plain. It shows some differences from the typical Pampean shallow lakes, such as high salinity and high arsenic and fluoride levels. The aim of this paper is to analyze the trace elements [arsenic (As), fluoride (F−) and vanadium (V)] present in Chasicó Lake. Surface and groundwater were sampled in dry and wet periods, during 2010 and 2011. Fluoride was determined with a selective electrode. As and V were determined by Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES). Significant correlation in surface water was only found for As and F− (r = 0.978, p < 0.01). The As, F− and V concentration values were higher and more widely dispersed in surface water than in groundwater, as a consequence of evaporation. The fact that these elements do not correlate in surface water may also indicates that groundwater would not be the main source of origin of As, F− and V in surface water. The origin of these trace elements is from volcanic glass from Pampean loess. As, F− and V concentration were higher than in national and international guideline levels for the protection of aquatic biota. Hence, this issue is relevant since the silverside (Odontesthes bonariensis) is the most important commercial species in Chasicó Lake. This fish is both consumed locally and exported to other South-American countries through commercial and sport fishing.